THE IMPACT OF INTEREST EXPENSES AND INTEREST INCOME ON THE NET PROFIT OF SOE BANKS LISTED ON THE IDX 2021 - Aulia, Aulia; Sari, Ayu Kurnia; Anggraini, Dian (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The purpose of this research is to ascertain how interest income and interest expenses affect net income from 2012 to 2020. The financial statements of Concise Profit and Loss for the years 2012 to 2020 were used as data sources for the quantitative research method. The data normality test and Pearson Product correlation analysis are utilized in the method of data analysis. Moment, the determination coefficient, and the analysis of multiple linear regression. Knowing the effect that Interest Income and Interest Expense have on Net Profit indicates, based on the findings of the data analysis, that the data are normally distributed, that the closeness of the relationship is 0.494 strong category, and that the influence is in the positive direction. Net Profit is affected by interest income and interest expenses by 85.4%, and other variables affect the remaining 14.4%. It is known that significant 0.000 0.05 and t count (6.088) are greater than t table (2.034). At state-owned banks listed on the Indonesia Stock Exchange, this indicates that interest income has a positive effect on net income, with significant 0.023 0.05 and t count (-2.382) greater than t table (2.034). This indicates that state-owned banks listed on the Indonesia Stock Exchange's net income is partially impacted by interest expense. Additionally, the F count is known to be 103.149  F table 3.28, with a significance level of 0.000  0.05. At state-owned banks listed on the Indonesia Stock Exchange, this demonstrates that all independent variables, specifically interest income and interest expense, have a significant impact on net income simultaneously.